1993
DOI: 10.1038/jcbfm.1993.110
|View full text |Cite
|
Sign up to set email alerts
|

Striatal 18F-DOPA Uptake: Absence of an Aging Effect

Abstract: L-[18F]6-Fluoro-DOPA (L-[18F]6-fluoro-3,4-dihydroxyphenylalanine; FDOPA) has been used with quantitative positron emission tomography (PET) to assess presynaptic nigrostriatal dopaminergic function in life. The relationship of estimated kinetic rate constants for striatal FDOPA uptake [Ki(FDOPA)] to the normal aging process has been the subject of conflicting reports. Resolution of this issue has been hampered by methodological differences in previous FDOPA/PET investigations. We studied 19 healthy normal subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 21 publications
5
34
1
Order By: Relevance
“…This difference in mean age could theoretically enhance the difference in 18 F-FDOPA uptake between patients and controls. However, 18 F-FDOPA uptake shows no or only a minimal decrease during aging (15,(28)(29)(30); therefore, it is unlikely that the small difference in the ages of the PD patients and the healthy controls in the present study would have affected the results.…”
Section: Discussioncontrasting
confidence: 38%
“…This difference in mean age could theoretically enhance the difference in 18 F-FDOPA uptake between patients and controls. However, 18 F-FDOPA uptake shows no or only a minimal decrease during aging (15,(28)(29)(30); therefore, it is unlikely that the small difference in the ages of the PD patients and the healthy controls in the present study would have affected the results.…”
Section: Discussioncontrasting
confidence: 38%
“…This is in agreement with others [15,38,39], although some studies have shown an ageing effect with F-DOPA PET [40,41]. This doubtful effect of ageing on F-DOPA uptake may perhaps be explained by a lack of AADC decline during ageing [42], which is supported by post-mortem studies, indicating no decrease in AADC activity with age [43].…”
Section: Discussionsupporting
confidence: 80%
“…Initial use of F-DOPA to examine age effects led to contradictory findings. Martin et al (1989) demonstrated a significant 8.3% per decade decrease in uptake of F-DOPA, but this was not comfirmed by later studies (Sawle et al, 1990;Eidelberg et al, 1993). In a methodologically rigorous study which controlled for the effects of peripheral metabolism, duration of scan acquisition times and striatal volume loss with ageing, Cordes et al (1994), reported a significant, albeit more modest decrease in F-DOPA uptake with age, of the order of 3.5% per decade.…”
Section: (I) Biosynthetic Enzymesmentioning
confidence: 59%